HEART TRANSPLANTATION IN DIABETIC RECIPIENTS - V. N. Poptsov; E. N. Zolotova (Вестник трансплантологии и искусственных органов)
Diabetes mellitus is one of the most prevalent chronic metabolic disorders. Its role in patients with heart transplantation is not unifi ed. According to some authors, post-transplantation diabetes mellitus increases the risk of acute rejections and infections, increases the incidence of coronary artery disease of the graft and reduces long-term survival of patients with heart transplantation. On the other hand other studies did not confi rm these fi ndings. However, when diabetic patients were stratifi ed by disease severity, recipients with less severe disease achieved better survival. Accordingly, posttransplant survival was not signifi cantly different between recipients with uncomplicated diabetes and nondiabetic recipients. Diabetes alone should not be a contraindication to heart transplantation. Well-selected diabetic patients achieve the same survival as nondiabetic patients. Conversely, patients with complicated diabetes have signifi cantly worse survival. Therefore, given the critical shortage of transplantable organs, maximal benefi t may be achieved by exploring alternative treatment options in individuals with severe diabetes. These include use of high-risk transplant lists and destination therapy.